Multi-walled carbon nanotubes and metal–organic framework nanocomposites as novel hybrid electrode materials for the determination of nano-molar levels of lead in a lab-on-valve format - Wang, Yang; Wu, Yichun; Xie, Jing; Ge, Huali; Hu, Xiaoya (Analyst (London), 2013)
Metal-organic frameworks have been the subject of intense research because of their unique physicochemical properties. The presented study investigates the application of multi-wall carbon nanotubes and metal-organic frameworks (MWCNTs@Cu3(BTC)2) nanoparticles-modified electrode for the determination of trace levels of lead. The nanocomposites were prepared by solvothermal synthesis and characterized in detail. The experimental procedure was carried out by accumulating lead on the electrode surface and subsequently measuring with differential pulse anodic stripping voltammetry in a lab-on-valve format. The main parameters affecting the analytical performance, including the amount of MWCNTs@Cu3(BTC)2 suspension, supporting electrolyte and its pH, stripping mode, and flow rate, have been investigated in detail. Under the optimum conditions, the oxidation peak current displayed a calibration response for lead over a concentration range from 1.0 × 10(-9) to 5.0 × 10(-8) mol L(-1) with a excellent detection limit of 7.9 × 10(-10) mol L(-1). The relative standard deviation of 7 successive scans was 3.10% for 1.0 × 10(-8) mol L(-1) lead. The established method showed a great improvement in sensitivity and sample throughput for lead analysis.